A review of the main placental histopathological findings in SARS-CoV-2 infection: analysis of COVID 19 positive patients - single center experience - Risteski, Vladimir; Tanevska Zrmanovska, Aneta; Kochoski, Goran; Kostadinova Kunovska, Slavica; Petrushevska, Gordana (Wiley, 2022)
Background: COVID-19, the disease caused by the novel coronavirus SARS-CoV-2, is a severe systemic thrombotic syndrome that emerged in 2019, with an ensuring pandemic. In so far postulated available literature there is a lack of clarity on the exact mechanism how the SARS-CoV-2 virus acts on the placenta. There is a direct effect on the placenta which leads to hypoxia and an indirect effect that is reflected through proinflammatory responses. Aims: To emphasize the spectrum of histopathological and transmission electron microscopy changes in the placenta of COVID infected pregnant women. Methods: The current study was designed as a prospective study on 39 pregnant women with SARSCoV-2 confirmed infection on nasopharyngeal samples. Gross dissection sampling was performed according to Amsterdam Placental criteria. The standard procedure of paraffin embedded section, stained with H&E was routinely used. Moreover the tissue was stained with immunohistochemistry to present the inflammatory response of the placenta, with the following antibodies: CD3, CD20 and CD68. Results & Conclusions: Histological studies of placental tissue revealed the presence of maternal vascular malperfusion (MVMs) or foetal vascular malperfusion (FVMs) lesions and mild inflammatory lesions. The most prevalent histopathological changes were decidual arteriopathy and increased perivillous f ibrin deposition. Ultrastructural analyses showed spherical-like coronavirus particleswithanelectron intermediate-density core as well projections from the surface as spike-like structures in the syncytiotrophoblasts. In conclusion, there are significant histomorphological changes that indicate maternal malperfusion.